HISTORISMS AS STYLISTIC AND PRAGMATIC DEVICES IN KHAYRIDDDIN SULTONOV'S PROSE (Eureka Journal of Education & Learning Technologies, 2026)
This article investigates the stylistic and pragmatic functions of historisms (istorizmlar) in the novellas of contemporary Uzbek writer Khayridddin Sultonov: Ko'ngil ozodadur (The Heart is Free), Yozning yolg'iz yodgori (The Lonely Memory of Summer), and Saodat sohili (The Shore of Happiness). Historisms — words denoting objects, phenomena, or social realities that have ceased to exist in contemporary life — are distinguished from archaisms on the basis that they retain their referential uniqueness: no modern synonym exists to replace them. Drawing on stylistic theory (Galperin 1971; Leech and Short 1981; Vinogradov 1963), Uzbek lexicology (Mirzayev 2010; Mahmudov 2002), and pragmatic frameworks (Safarov 2008; Hakimov 2001), the study demonstrates that Sultonov employs historisms not merely for historical colouring but as instruments of characterisation, temporal contrast, irony, and ideological commentary. The findings reveal that historisms in Sultonov's prose function as pragmatic presupposition triggers, evoking shared cultural memory and constructing an implicit dialogue between past and present. The study contributes to Uzbek literary linguistics and offers a model for the pragmatic analysis of archaic lexical strata in contemporary prose.
Keywords: Historisms; istorizmlar; archaic lexis; Khayridddin Sultonov; Uzbek prose; stylistics; pragmatics; presupposition; temporal contrast; linguistic personality.